Access to finance and innovative activity of EU firms: A cluster analysis - Annalisa Ferrando; Senad Lekpek (European Investment Bank (EIB), 2018)
The way firms finance their investments can potentially explain the heterogeneity of firms in terms of their innovation. We use a novel firm-level survey of the European Investment Bank (EIBIS) which provides information about a wide range of financing sources that firms use to fund their investment activities. The aforementioned survey also reveals a firms' degree of innovativeness. By applying a cluster analysis to group firms using information on their financing decisions, we investigate the link between finance and innovation of EU firms. We identify seven financing clusters to show that the degree of innovativeness (defined in terms of R&D or software investment, R&D and software turnover ratios, and the introduction of new products) increases with the diversification of financial instruments. Firms that use several financing instruments are more likely to invest in R&D and software activities and develop new products compared to firms that use a more limited number of financing instruments.
Keywords: D22; G32; O31; 330; innovation; R&D; internal and external finance; cluster analysis